2006
DOI: 10.1007/s00192-006-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of prolapsed vaginal tissue in pre- and postmenopausal women

Abstract: The aim of this study was to explore the relationship between biomechanical properties and the occurrence of pelvic organ prolapse (POP) through analysis on biomechanical properties of vaginal tissue. The biopsy specimens were obtained from 43 patients undergoing transvaginal hysterectomy, who were assigned into premenopausal POP, postmenopausal POP, premenopausal control and postmenopausal control groups. Tissue specimens were biomechanically assessed by a purpose-built tissue puller system, and stress-strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 15 publications
11
87
0
6
Order By: Relevance
“…Previous biomechanical study has also demonstrated that women with prolapse have stiffer vaginal tissues. 38 In contrast, Moalli et al, 31 found increased collagen III in the subepithelial layers of the vaginal wall. These inconsistencies may arise from the following: (i) different methods used to assess collagen quality; and (ii) different biopsy sites from which the collagen samples were obtained.…”
Section: Studies Of Collagen Composition In Vaginal Wallmentioning
confidence: 95%
“…Previous biomechanical study has also demonstrated that women with prolapse have stiffer vaginal tissues. 38 In contrast, Moalli et al, 31 found increased collagen III in the subepithelial layers of the vaginal wall. These inconsistencies may arise from the following: (i) different methods used to assess collagen quality; and (ii) different biopsy sites from which the collagen samples were obtained.…”
Section: Studies Of Collagen Composition In Vaginal Wallmentioning
confidence: 95%
“…Tissues from women without prolapse were not tested (14). Lei, et al described significant differences between pre-and postmenopausal women with and without prolapse; in general, prolapse conferred less elasticity and greater stiffness although vaginal tissues from women with severe prolapse exhibited low forces at failure (15). A third study showed marked variability in maximal strength and strain with no discernable trends in biomechanical properties of vaginal samples taken from 16 postmenopausal women with prolapse (16).…”
Section: Changes With Prolapsementioning
confidence: 99%
“…Precise etiology of uterovaginal prolapse is not known but likely to be multifactorial. The severity of prolapse may vary with different risk factors [8][9][10].…”
Section: Introductionmentioning
confidence: 99%